Acute exposure to organic and inorganic sources of copper: Differential response in intestinal cell lines. Issue 8 (20th October 2018) - Keenan, Joanne; O'Sullivan, Finbarr; Henry, Michael; Breen, Laura; Doolan, Padraig; Sinkunaite, Indre; Meleady, Paula; Clynes, Martin; Horgan, Karina; Murphy, Richard
Abstract: Scope: Copper supplementation in nutrition has evolved from using inorganic mineral salts to organically chelated minerals but with limited knowledge of the impact at the cellular level. Methods: Here, the impact of inorganic and organic nutrient forms (glycinate, organic acid, and proteinate) of copper on the cellular level is investigated on intestinal cell lines, HT29 and Caco‐2, after a 2‐hr acute exposure to copper compounds and following a 10‐hr recovery. Results: Following the 10‐hr recovery, increases were observed in proteins involved in metal binding (metallothioneins) and antioxidant response (sulfiredoxin 1 and heme oxygenase 1), and global proteomic analysis suggested recruitment of the unfolded protein response and proteosomal overloading. Copper organic acid chelate, the only treatment to show striking and sustained reactive oxygen species generation, had the greatest impact on ubiquitinated proteins, reduced autophagy, and increased aggresome formation, reducing growth in both cell lines. The least effect was noted in copper proteinate with negligible impact on aggresome formation or extended growth for either cell line. Conclusion: The type and source of copper can impact significantly at the cellular level. Abstract : Evaluating organic compounds as nutritional replacements for inorganic copper revealed Cu OAC (copper organic acid chelate) to induce sustained reactive oxygen species, leading to proteosomal stress, reduced autophagy and increased aggresome formation (red stain close to nucleus), and ultimately impacted on cell growth. Copper glycinate and inorganic copper sulphate showed sporadic aggresome formation. Copper proteinate caused no aggresome formation and no growth reduction (Caco‐2 and HT29).